Glacier-Induced Alluvial Fan Development on the Northeast Tibetan Plateau Since the Late Pleistocene - An, Fuyuan; BadingQiuying; Li, Shanlu; Gao, Donglin; Chen, Tianyuan; Cong, Lu; Zhang, Jinhu; Cheng, Xiali (Frontiers in Earth Science, 2021)
The origin of alluvial fans at the drainage basin or the margins of the arid sedimentary basin on the northeastern Tibetan Plateau (NETP) has been a focus of debate among scientific communities. Extensive alluvial fans had developed in the mountain-basin systems of this region during the late Pleistocene. Based on geomorphic/stratigraphic studies and the optically stimulated luminescence (OSL) chronology, we investigated numerous alluvial sequences in the drainage basin of the coupled mountain-basin system on the NETP. Sedimentologic analyses showed that these alluvial sediments mainly comprise crudely meter and decimeter beds of fanglomerate and sandy lenticles, which occasionally contain boulders in the thinner layers. OSL dating results showed that the alluvial sediments were mainly developed during the late MIS 5, MIS 3, and Last Glaciation and Deglaciation (maximum aggradations), while little had occurred during the early Holocene. Comparing our ages and their probability density curves with those of glacial advances from the northeastern/eastern TP, the consistency of both records during different stages since the late Pleistocene suggested that the development of alluvial fans was driven by glacier activities, which yielded abundant outwash, feeding alluvial aggradations. Based on this finding, together with results of previous studies, we argued that the dynamics of alluvial geomorphic processes had a paleoclimatic origin rather than surface uplifts. Further studies indicated that the precipitation of glaciations originated from the ISM northward intrusion during the late MIS 5, MIS 3, and Holocene; however, it was mainly influenced by the westerlies during the Last Glaciation and Deglaciation. Therefore, the development of alluvial fans on the NETP represents coupling signals of the ISM and the westerlies on the interglacial–glacial cycle timescales. The coupling evolution of glacier activities and alluvial aggradations in the drainage basins of mountain-basin systems on the NETP provides a model for assessing the linkages between regional geomorphic processes and atmospheric circulations on hemispheric scales.